Long-term prognosis of type 1 diabetes in relation to the clinical characteristics at the onset of diabetes - M.H. Elsamahy; Y.I. Elhenawy; N. Altayeb (SpringerOpen, 2017)
Introduction: It is known that age, the degree of glycemic deterioration and the immune status at the time of the onset of type 1 diabetes (T1DM) are objective factors that can predict the residual B-cell function and the glycemic control 1 year after diagnosis. Objective: Evaluation of the long-term prognosis of T1DM in relation to the clinical characteristics at the time of diabetes onset. Methods: An observational retrospective study conducted on 200 patients including all the patients with newly diagnosed T1DM in the period from 2003 to 2013. Results: Fifty-three percent of the studied cohort presented initially by diabetic ketoacidosis (DKA). The current studied cohort showed that younger patients required more insulin during follow-up. Female patients needed higher insulin doses at 8 and 10 years after diagnosis, yet no difference among both genders during early years of follow up. Patients presenting with DKA required higher insulin requirements over the first 2 years and poor glycemic control. C-peptide levels at diagnosis correlated with insulin requirements during the first 2 years. Insulin dose at onset correlated positively with the insulin dose over the entire follow up period. A positive correlation was found between HbA1c at onset and 1, 2 and 4 year. Conclusion: Female gender, younger age, presence of DKA, lower C-peptide and higher HbA1c at onset could predict a poor long-term outcome. Identification of factors related to a worse outcome of T1DM at the onset of diabetes might help in selecting those patients who should be given more intensive treatment.